Assessment of surgical outcome in general surgery using Portsmouth possum scoring - Tejaswini Vallabha; Manish Pangi (Al Ameen Medical College, 2013)
Objective: The Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM) and its modification, Portsmouth POSSUM, are considered as methods of risk scoring. Application of this scoring system helps in assessing the quality of the health care provided& surgical outcome. Its utilization in our country where the level of healthcare and resources differ is limited. Hence, a prospective study to assess the outcome of surgeries using P Possum scoring system in a teaching hospital at district level and compare with other health care facilities with similar and different settings was taken up. Methods: 175 major surgeries were studied. Using P-POSSUM equation, predicted mortality rates were calculated & compared with the actual outcome. The predicted mortality & actual outcome was compared with other studies done in similar and different health care levels. Results: An observed to expected ratio of 0.96 was obtained, indicating there was no significant difference between expected to observed mortality rates suggesting a reasonably good quality of outcome in comparison with other health care systems. Conclusion: The quality of surgical care provided and surgical outcome are comparable to other health care systems with observed to expected mortality ratio being nearly same. P Possum can be used as a tool for outcome audits.